肝内胆汁うっ滞および関連肝疾患の治療 (2022)
【課題】ＵＤＣＡ治療では、疾患重症度にかかわらずＩＣＰの生化学的マーカーがある程度改善されたが、掻痒の顕著な軽減および血清胆汁酸の著しい減少は重度のＩＣＰ（胆汁酸濃度≧４０μｍｏｌ／Ｌ）患者に限って認められたことから、さらに効果的な治療が必要とされる。【解決手段】本発明は、それを必要とする被験体の肝内胆汁うっ滞を治療するか、そのリスクを低減する方法であって、胆汁酸脱抱合／加水分解活性および／または７－エピマー化活性を有する少なくとも１つの細菌種または株を含む組成物の治療有効量を被験体に投与し、それにより、それを必要とする被験体の肝内胆汁うっ滞を治療するか、そのリスクを低減することを含む方法に関する。また、そのような方法に使用するための組成物も提供される。【選択図】なし The invention is directed to a method of treating or reducing the risk of intrahepatic cholestasis in a subject in need thereof, comprising administering to the subject a therapeutically effective amount of a composition comprising at least one bacterial species or strain comprising bile acid deconjugation/hydrolysis activity and/or 7-epimerization activity, thereby treating or reducing the risk of intrahepatic cholestasis in a subject in need thereof. Compositions for use in such methods are also provided.